Efeitos da associação da clonidina à ropivacaína na anestesia peridural - Azevedo Alves, Túlio César [UNESP] (2002)
Background and Objectives - Clinical effects and the potential synergism between clonidine an α 2-adrenergic agonist and ropivacaine have not been studied in patients undergoing epidural anesthesia. This research aimed at clinically evaluating clonidine associated to ropivacaine for epidural anesthesia. Methods - Participated in this double-blind study 60 patients of both genders who were distributed in two groups: G control = epidural 0.75% ropivacaine (150 mg); G clonidine = epidural 0.75% ropivacaine (150 mg) plus clonidine (300 μg). The following parameters were studied: total analgesic block (onset time), motor block onset, analgesic and motor block duration upper level of analgesia, consciousness level, need for intraoperative analgesia and supplemental sedation, peri and postoperative arterial hypotension, intensity of postoperative pain, analgesia duration, and side-effects. Results - Epidural clonidine (300 μg) had not affected onset (p > 0.05) but has prolonged sensory and motor block duration (p < 0.0007) and postoperative analgesia (p > 0.001). Arterial hypotension rate was the same for both groups, but the incidence of bradycardia and sedation was higher in the clonidine group (p < 0.02 and p < 0.001 respectively). Shivering was more common in the control group (p < 0.001). Conclusions - In the conditions of our study there has been a clear synergism between epidural clonidine and ropivacaine. Clonidine increases sensory and motor block duration during epidural anesthesia with ropivacaine and prolongs postoperative analgesia. Additional advantages of clonidine are increased sedation and decreased shivering, but its drawback is to increase the incidence of bradycardia.